2012
DOI: 10.1186/1756-3305-5-235
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oviposition-site deprivation on Anopheles gambiae reproduction

Abstract: BackgroundThe African malaria mosquito, Anopheles gambiae, depends on availability of suitable surface water for oviposition. Short and long dry spells occur throughout the year in many parts of its range that limit its access to oviposition sites. Although not well understood, oviposition-site deprivation has been found to rapidly reduce egg batch size and hatch rate of several mosquito species. We conducted laboratory experiments to assess these effects of oviposition-site deprivation on An. gambiae and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
(14 reference statements)
0
33
0
Order By: Relevance
“…Consistent with aestivation rather than with quiescence, the switch from reproduction to long-term survival was not a direct result of the absence of surface water for oviposition (Artis et al, 2014; Dieter et al, 2012), indicating that a token environmental stimulus is involved. Accordingly, An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with aestivation rather than with quiescence, the switch from reproduction to long-term survival was not a direct result of the absence of surface water for oviposition (Artis et al, 2014; Dieter et al, 2012), indicating that a token environmental stimulus is involved. Accordingly, An.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, studies using the G3 colony of An. gambiae showed that oviposition-site deprivation alone was insufficient to shift mosquitoes into reproductive quiescence and extended longevity (Artis et al, 2014; Dieter et al, 2012). During the dry season, Anopheles funestus exhibited a reduced proportion of gravid females and a higher proportion of partly blood-fed females compared with wet season, suggesting that reproduction is suppressed in at least a fraction of the population (Charlwood et al, 2013).…”
Section: Changes In Reproduction and Blood-feedingmentioning
confidence: 99%
“…Blood and sugar access were arbitrarily provided per treatment on different schedules as described below (Table 2). Based on our insectary blood-feeding schedule of once per 7 days, this interval was selected as the standard for non-restricted blood diet [73, 74]. Blood meals took place between 5–6 pm in a darkened room at 27 °C, 80% RH.…”
Section: Methodsmentioning
confidence: 99%
“…Dry-season treatments (50% RH) were not provided with oviposition water, i.e. were subjected to oviposition site deprivation [74]. Handling and maintenance of the cages was minimized as much as possible to reduce human interference and subsequent stress in the mosquitoes.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we test whether Plasmodium-infected mosquitoes oviposit earlier than their non-infected counterparts. To do so, we use the Culex pipiens-Plasmodium relictum system, which combines a mosquito characterized by its strong flexibility regarding the timing of egg-laying [9,10] and a parasite that drastically reduces its fecundity [3]. Bringing forward the age of oviposition is expected to come at a cost, which only the fittest mosquitoes may be able to bear.…”
Section: Introductionmentioning
confidence: 99%